Pemeriksaan Kesehatan Lansia di Masa Pandemi Covid-19 di Posyandu Ngudi Waras Semanggi RW XII Surakarta - Siti Sarifah; Yuli Widyastuti (Masyarakat Berkarya : Jurnal Pengabdian dan Perubahan Sosial, 2024)
The COVID-19 pandemic has significantly impacted elderly health, requiring regular medical check-ups to monitor their condition. This study examines the health examinations of the elderly at Posyandu Ngudi Waras, Semanggi RW XII, Surakarta, during the pandemic. The research aims to assess the frequency of health check-ups, key health indicators such as blood pressure, oxygen saturation, blood sugar levels, and body mass index, as well as the challenges faced in providing healthcare services for the elderly. Using a descriptive quantitative approach, data were collected through medical records and interviews with healthcare providers and elderly participants. The results indicate that despite pandemic-related restrictions, routine health monitoring continued with adjustments to health protocols. The findings highlight the importance of community-based health services in ensuring the well-being of the elderly, particularly during health crises. Strengthening health programs for the elderly, enhancing accessibility, and improving awareness of preventive healthcare are essential for maintaining their quality of life.